Correcting the cut-off point of hemoglobin at high altitude favors misclassification of anemia, erythrocytosis and excessive erythrocytosis - Gonzales, GF (2018)
The World Health Organization (WHO) defines anemia according age, gender, and altitude based on statistical distribution considerations and by cut‐off points. Anemia in pregnancy and in children aged 6–59 months is defined as hemoglobin (Hb) concentration <11 g/dL. Since Hb contains almost 70% of iron in the organism, WHO recommends its measurement to determining prevalence of anemia as screening for iron deficiency (ID) despite that they recognize that anemia is not a specific indication of ID...